Impact of severe valvular heart disease in adult congenital heart disease patients - Graziani, Francesca; Iannaccone, Giulia; Meucci, Maria Chiara; Lillo, Rosa; Delogu, Angelica Bibiana; Grandinetti, Maria; Perri, Gianluigi; Galletti, Lorenzo; Amodeo, Antonio; Butera, Gianfranco; Secinaro, Aurelio; Lombardo, Antonella; et al. (Frontiers in Cardiovascular Medicine, 2022)
BACKGROUND: The clinical impact of valvular heart disease (VHD) in adult congenital heart disease (ACHD) patients is unascertained. Aim of our study was to assess the prevalence and clinical impact of severe VHD (S-VHD) in a real-world contemporary cohort of ACHD patients. METHODS: Consecutive patients followed-up at our ACHD Outpatient Clinic from September 2014 to February 2021 were enrolled. Clinical characteristics and echocardiographic data were prospectively entered into a digitalized medical records database. VHD at the first evaluation was assessed and graded according to VHD guidelines. Clinical data at follow-up were collected . The study endpoint was the occurrence of cardiac mortality and/or unplanned cardiac hospitalization during follow-up. RESULTS: A total of 390 patients (median age 34 years, 49% males) were included and S-VHD was present in 101 (25.9%) patients. Over a median follow-up time of 26 months (IQR: 12-48), the study composite endpoint occurred in 76 patients (19.5%). The cumulative endpoint-free survival was significantly lower in patients with S-VHD vs patients with non-severe VHD (Log rank p <0.001). At multivariable analysis, age and atrial fibrillation at first visit (p=0.029 and p=0.006 respectively), lower %Sat O2, higher NYHA class (p=0.005 for both), lower LVEF (p=0.008) and S-VHD (p=0.015) were independently associated to the study endpoint. The likelihood ratio test demonstrated that S-VHD added significant prognostic value (p=0.017) to a multivariate model including age, severe CHD, atrial fibrillation, %Sat O2, NYHA, LVEF and right ventricle systolic pressure>45 mmHg. CONCLUSION: In ACHD patients, the presence of S-VHD is independently associated with the occurrence of cardiovascular mortality and hospitalization. The prognostic value of S-VHD is incremental above other established prognostic markers.